Design and analysis of a novel quadrotor with a two-axes propeller rotation - Tan, Shi Yin (2019)
This report serves to document the development and design process of a fault tolerant Unmanned Aerial Vehicle (UAV), specifically a quadrotor, utilizing the independent command of 2 degree of freedom (DOF) rotation from each propeller. The report details the design of the augmented UAV propeller in which a propeller with two-axes of rotation is implemented in order to achieve control over 2-DoF motion of the propeller. Various design iterations and concepts are also explored and compared. The stress and deformation analysis of each design is also detailed in this report. The report then concludes with the various design improvements that can be considered moving forward in the optimization and refinement process for the fault tolerant UAV.